PEMENUHAN HAK KESEHATAN DAN MAKANAN YANG LAYAK BAGI NARAPIDANA BERDASARKAN PERATURAN PEMERINTAH NOMOR 32 TAHUN 1999 TENTANG SYARAT DAN TATA CARA PELAKSANAAN HAK WARGA BINAAN PEMASYARAKATAN (Studi Kasus di Lembaga Pemasyarakatan Perempuan Kelas IIA Pekanbaru) - Puspa Valentin; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Government regulation no. 32 in 1999 governed the requirements and ordinances for the administration of the rights of the human rights of the correctional community. Pp no. 32 in 1999 provided the optimum services needed to achieve the goals of the correctional facility. In the fight to achieve health asa human right, the government has a duty and authority to bring good health to its citizens, including prisoners. Studies have shown that the application of rights to health care and food to prisoners has not run high because of the absence of medical personnel such as doctors and nonmedical health facilities that are available in polyikinic. In reality the health services that are in the iia new women's correctional institute are inadequate and have not met the established standards.This type of study is empirical juridical or sociological law study an approach that emphasizes legal aspects of the subject as to what will be discussed, is related to the reality in the field. The study was conducted in the new iia class women's correctional facility, while the sample population was the whole party that dealt with the problem in question. The source of the data used is primary and secondary data collection, the technique of data collection in this study is observation, questionings, interviews and review of populationaanjenis this study is an empirical judical or sociological study of the study's approach to law that defines the legal aspect of the subject subject to be discussed, linked to the reality of the field. The study was conducted in the new iia class women's correctional facility, while the sample population was the whole party that dealt with the problem in question. The primary and secondary data collection techniques in the study are observ, questionnaire, interviews and literature studies.Keywords: Government Regulation-Women's Correctional InstitutionHealth rights and proper food for prisoners